Reference Architecture and Agile Development Method for a Process-Driven Web Platform based on the BPMN-Standard and Process Engines - Schäffer, Eike; Schobert, Marvin; Reichenstein, Tobias; Selmaier, Andreas; Stiehl, Volker; Herhoffer, Markus; Mala, Matûs; Franke, Jörg (CIRPe 2021 Sustainable, resilient, and agile manufacturing and service operations: Lessons from COVID-19, 2021)
One of the major trends in the 21st century is the trend towards digital transformation within Industry 4.0. In order to adapt to high volatile market conditions, especially in the context of COVID-19, companies do not only have to transfer their knowledge into digital systems. Furthermore, they have to be able to tailor their business processes rapidly to changing customer’s needs. The implementation of efficient and transparent processes is thereby known as the process of digital transformation and requires its underlying software-architecture to be highly flexible and scalable. Especially a web-based platform represents a highly user-centered application for multi-user purposes and can quickly adapt to its customer needs. While e-commerce and video-streaming platforms, like eBay or Netflix, often already provide a highly flexible, microservice-based architecture, common tools and platforms within the engineering-domain are usually still based on rather monolithic or service-oriented architectures (SOA). Therefore, an adaption to changing market conditions and the integration of proprietary tools is often technically demanding and economically not feasible, especially for small and medium-sized enterprises (SME). In this context, the so-called Process-Driven-Approach (PDA) offers a sustainable and tool-neutral blue-print for a system’s architecture strictly following the separations-of-concerns principle and allowing a user-centered layout. The PDA enables the integration of business processes and tools within an orchestrating framework, provided by a process engine. While the PDA within the engineering domain has been presented in a preceding paper, this paper supposes a reference architecture and agile development method for engineering-platforms via the PDA based on the BPMN-standard and process engines. These concepts are validated by a prototypical implementation of a platform-demonstrator for tool-supported planning of robot-based automation solutions.<br
Keywords: Process-Driven web platform; reference architecture; ROBOTOP; Process-Driven-Approach; PDA; agile; user-centered; development method

Unveiling Causality in Stateful Enterprise Knowledge Graphs: An Exploration of Process-Driven Object Relationships - Schobert, Marvin; Mala, Matúš; Herhoffer, Markus; Farag, Samuel; Franke, Jörg (Procedia CIRP, 2024)
The exponential growth of enterprise data generation demands innovative approaches for efficient information management across highly interconnected domains. Particularly, the process of systems engineering involves inhomogeneous data sets requiring a high degree of flexibility and traceability throughout its lifecycle. While structured data resides comfortably in dedicated systems, managing unstructured information within annotations, documents and emails often comes with challenging holistic comprehension of linking, context and revisioning. Graph technology holds promise in establishing adaptable connections among decentralized data sets. However, leveraging graph databases comes with challenges. Schema standardization, crucial for framing complex processes, is a difficult undertaking due to evolving data interrelationships and changing requirements. This paper proposes a two-fold solution. First, we introduce a conceptual schema that decouples stateful object descriptions from its headers and furthermore documents transactions. This allows flexible object associations, conditional state versioning and improved traceability while maintaining manageability. Second, we leverage the Business Process Model and Notation (BPMN) for process design, service orchestration and automated graph manipulations. Through application to the publicly available Northwind data set using neo4j and Flowable BPM, we illustrate our methodology's efficacy and the seamless integration of type-safer data science into dynamic knowledge graphs, contributing to the future of enterprise data management.
CRIS-Team Scopus Importer:2024-11-22
Keywords: BPMN; Design informatics; Knowledge Graphs; neo4j; Provenance